O sistema de transitividade no inglês e no português brasileiro: caracterização da função circunstância com base em textos originais e traduzidos - Aline Barreto Costa Braga (2016)
This thesis draws on Systemic Functional Linguistics (SFL) (HALLIDAY; MATTHIESSEN, 2014) oriented towards Translation Studies (HOLMES; 2000 [1972]) and reports on a study aimed at characterizing CIRCUMSTANCES in translated CLAUSES selected from eight different text categories (Research Article, Political Speech, Popular Science, Fiction, Instructions Manual, Tourism Leaflet, Review and Educational Website). The texts were English source texts and their translations into Brazilian Portuguese and Brazilian Portuguese source texts and their translations into English retrieved from Klapt!, an English/Brazilian Portuguese bidirectional parallel and comparable corpus. The CLAUSES extracted from the texts were manually annotated in spreadsheets to indicate the presence or absence of CIRCUMSTANCES. CLAUSES with CIRCUMSTANCES were compiled in new spreadsheets and annotated according to type of CIRCUMSTANCE, REALIZATION of CIRCUMSTANCE, CLAUSE type and THEMATIC POSITION in order to observe patterns in each of the text categories and identify shifts in translation equivalents (CATFORD, 1965; MATTHIESSEN, 2001). The spreadsheets were analysed through scripts in the R software environment (R CORE TEAM, 2015) to compute the frequency of the categories and shifts. The results showed that in both languages (English and Portuguese), the most frequent type of CIRCUMSTANCE were CIRCUMSTANCES of LOCATION (PLACE and TIME); the most frequent type of CLAUSE presenting CIRCUMSTANCES were MATERIAL and RELATIONAL CLAUSES and the most frequent REALIZATION of CIRCUMSTANCES were PREPOSITIONAL PHRASES and ADVERBIAL GROUPS. CIRCUMSTANCES were also more frequent in THEMATIC POSITION in CLAUSES in Portuguese source texts and more frequent in NON-THEMATIC POSITION in English source texts. The text categories having the largest number of CIRCUMSTANCES were the same on both languages. For CLAUSES in English source texts and their translation into Portuguese, Fiction and Instructions Manual presented the highest number of CIRCUMSTANCES. For CLAUSES in Portuguese source texts and their translation into English, both Research Article and Tourism Leaflet were the text categories with the largest number of CIRCUMSTANCES. The analysis of translation equivalents showed that CIRCUMSTANCES OF LOCATION and EXTENT presented more SHIFTS. The most frequent type of SHIFT was CIRCUMSTANCES REALIZED by PREPOSITIONAL PHRASES translated into CIRCUMSTANCES REALIZED by GROUPS (ADVERBIAL and NOMINAL GROUPS).